Clinical and economic outcomes in patients at risk of venous thromboembolism receiving appropriate enoxaparin or unfractionated heparin prophylaxis - Amin, Alpesh N.; Lin, Jay; Lenhart, Greg; Schulman, Kathy L. (Thrombosis and Haemostasis, 2009)
Clinical and economic outcomes were compared following appropriate prophylaxis with enoxaparin or unfractionated heparin (UFH) in a large, real-world population of US hospitalised medical and surgical patients at risk of venous thromboembolism (VTE). Discharges from the Thomson Reuters MarketScan® Hospital Drug Database (January 2004–March 2007) of patients aged ≥40 years, at risk of VTE according to the 7th American College of Chest Physicians (ACCP) guidelines, who spent ≥6 days in hospital and received appropriate ACCP-recommended enoxaparin or UFH prophylaxis were included. Patients with contraindications to anticoagulation were excluded. Hospital-acquired VTE, adverse events, and hospital costs for enoxaparin versus UFH were compared using univariate and multivariate analyses. Of the 5,136 discharges included, 4,014 (78%) received enoxaparin and 1,122 (22%) received UFH. Compared with UFH, enoxaparin was associated with significantly lower risk of hospital-acquired VTE (adjusted odds ratio [OR] 0.51, 95% confidence interval [CI] 0.30–0.86, p=0.012), pulmonary embolism (adjusted OR 0.33, 95% CI 0.14–0.79, p=0.013) or adverse events (adjusted OR 0.73, 95% CI 0.54–0.98, p=0.034). Total hospital costs per discharge were lower for enoxaparin (US $16,865 ± 10,979) than UFH (US $19,252 ± 14,970), with a mean difference of US $2,388 in favour of enoxaparin (p<0.001) (adjusted difference US $439, 95% CI US $ -39 to 909, p=0.072). In patients at risk of VTE, appropriate enoxaparin prophylaxis was associated with a reduction in hospital-acquired VTE, adverse events, and costs compared with appropriate UFH prophylaxis. Increased appropriate use of enoxaparin in patients at risk of VTE may help to reduce the clinical and economic burden of this condition.
Keywords: Venous thromboembolism; enoxaparin; unfractionated heparin; prophylaxis